Manajemen penanganan hasil tangkapan pada kapal pukat cincin mini di perairan Laut Jawa : Management of catch handling on mini purse seine vessels in the Java Sea - Irawan, Andi; Misuari, Muhammad Nur; Alamsyah, Heru Kurniawan; Rahmansyah, Fachrurizal Devlyn; Robet Perangin (Universitas Sam Ratulangi, 2025)
Fish caught on board must be processed carefully to ensure their quality meets desired standards. Proper handling of the catch is a crucial factor affecting the freshness and quality of fish. Conversely, poor handling may result in low catch quality. This study aims to analyze the suitability of handling and storage techniques using the bulking method, catch composition, and the compliance level of fishermen in handling fish catches on board, based on Minister of Marine Affairs and Fisheries Regulation No. 7 Article 6 of 2019, in the Central Java Sea. Data were collected throught direct observation on the KM Sinar Mandiri purse seine vessel and analyzed descriptively. The catch composition on KM Sinar Mandiri consisted mainly of Decapterus sp. 49%, followed by Euthynnus affinis 41%, Parastromateus niger 6%, and Loligo sp 4%. Observations showed that handling practies on KM Sinar Mandiri did not fully comly with Permen KP No. 7/2019 Article 6. Deficiencies included the absence of a special storage area for chemicals, cleaning and packaging materials, the use of ice not meeting hygine standars, and no pest identification program. As a result, the compliance level in handling fish catches was only 57%.